Justification of the application of physical therapy in youth with arterial hypertension - Ivanko, O. H.; Tovma, A. V.; Patsera, M. V.; Skrypnykova, Y. S.; Іванько, Олег Григорович; Товма, Анастасія Володимирівна; Пацера, Марина Вікторівна; Скрипникова, Яніна Семенівна (My University, 2021)
Over recent decades, a steady increase in arterial hypertension (AH) has been observed among the adult population of the world. It is known that this disease first occurs in adolescence. The prevalence of AH among school-age children varies from 2.4 to 14%, and can reach 18% among adolescents [1, p. 27]. The factors of elevated blood pressure (BP) among young people are psycho-emotional and informational loads, irrational diet with excessive consumption of salt, sedentary lifestyle, smoking, hereditary predisposition, and others. [2, p. 53]. An important fact is that adolescents do not feel sick and almost do not seek medical assistance when their BP begins to rise. Therefore, the timely start of the diagnosis of AH, treatment and prevention of cardiovascular complications is important [3, p. 48].